Every catholic child in a catholic school: historical resistance to state schooling, contemporary private competition, and student achievement across countries - Martin R. West; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2008)
Nineteenth-Century Catholic doctrine strongly opposed state schooling. We show that countries with larger shares of Catholics in 1900 (but without a Catholic state religion) tend to have larger shares of privately operated schools even today. We use this historical pattern as a natural experiment to estimate the causal effect of contemporary private competition on student achievement in cross-country student-level analyses. Our results show that larger shares of privately operated schools lead to better student achievement in mathematics, science, and reading and to lower total education spending, even after controlling for current Catholic shares.
Keywords: I20; L33; N30; Z12; 330; Private school competition; student achievement; Catholic schools; Privatschule; Katholizismus; Region; Allgemeinbildende Schule; Wettbewerb; Bildungsniveau; OECD-Staaten